Penggunaan Media Blok Pecahan untuk Meningkatkan Hasil Belajar Penjumlahan dan Pengurangan Bilangan Pecahan Siswa Kelas V - Lestari, Nanik Puji Sri (Jurnal Kualita Pendidikan, 2024)
This research was conducted at Pasir 3 Elementary School, Mijen District, Demak Regency in Class V with 27 students, as the background of the problem is the low value of this material from the KKM, the teacher's ability to teach only with existing methods, the purpose of this study is to improve learning outcomes on the Addition and Subtraction Operation Material of Fractions with Unlike Denominators Through Fraction Block Media. Classroom action research or Action Research. The actions taken in this study were 2 cycles where each cycle had 2 meetings. Data were collected using observation sheets and learning outcome tests carried out at the end of the cycle. The results achieved from this study were an increase in student learning outcomes on the Addition and Subtraction Operation Material of Fractions with Unlike Denominators which were seen to have increased after continuous practice and supervision through the Implementation of Fraction Block Teaching Aids. This can be proven by the final test scores of students in cycle 1 proven by an average score of 53.3 with a completion of 37.04%, increasing ability to increase the results of children's achievements in cycle 2 with an average score of 90 with a completion of 88.88%. The results of this study indicate that the use of Through Fraction Block Media on the Material of Arithmetic Operations of Addition and Subtraction of Fractions with Dissimilar Denominators provides a picture of a significant increase in learning outcomes towards the ability to understand students' learning outcomes. Based on these findings, it is suggested to teachers that the media applied by researchers can be used as an alternative in order to improve the ability to understand concepts or materials in the field of Mathematics Studies and do not stop trying and applying models, techniques or the use of teaching aids in the teaching and learning process.